The Immunological Synapse: An Emerging Target for Immune Evasion by Bacterial Pathogens - Capitani, Nagaja; Baldari, Cosima T. (Frontiers in Immunology, 2022)
Similar to other pathogens, bacteria have developed during their evolution a variety of mechanisms to overcome both innate and acquired immunity, accounting for their ability to cause disease or chronic infections. The mechanisms exploited for this critical function act by targeting conserved structures or pathways that regulate the host immune response. A strategic potential target is the immunological synapse (IS), a highly specialized structure that forms at the interface between antigen presenting cells (APC) and T lymphocytes and is required for the establishment of an effective T cell response to the infectious agent and for the development of long-lasting T cell memory. While a variety of bacterial pathogens are known to impair or subvert cellular processes essential for antigen processing and presentation, on which IS assembly depends, it is only recently that the possibility that IS may be a direct target of bacterial virulence factors has been considered. Emerging evidence strongly supports this notion, highlighting IS targeting as a powerful, novel means of immune evasion by bacterial pathogens. In this review we will present a brief overview of the mechanisms used by bacteria to affect IS assembly by targeting APCs. We will then summarize what has emerged from the current handful of studies that have addressed the direct impact of bacterial virulence factors on IS assembly in T cells and, based on the strategic cellular processes targeted by these factors in other cell types, highlight potential IS-related vulnerabilities that could be exploited by these pathogens to evade T cell mediated immunity.